2022
DOI: 10.1007/s13753-022-00445-y
|View full text |Cite
|
Sign up to set email alerts
|

Network Structure Optimization Method for Urban Drainage Systems Considering Pipeline Redundancies

Abstract: Redundancy is an important attribute of a resilient urban drainage system. While there is a lack of knowledge on where to increase redundancy and its contribution to resilience, this study developed a framework for the optimal network structure of urban drainage systems that considers pipeline redundancies. Graph theory and adaptive genetic algorithms were used to obtain the initial layout and design of the urban drainage system. The introduction of additional water paths (in loop)/redundancies is suggested by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Lu et al [21], in a comparative study of branched and looped drainage pipes in Dongying, China, found that the peak runoff at the outlets of looped systems was significantly lower than that of branched networks. Subsequently, Lu et al [22] developed a framework for the optimal network structure of UDSs considering pipe redundancy, and the results showed that the total overflow volume of UDSs with looped pipes was reduced by 20% to 30%. Reyes-Silva et al [23] described the topological structure of drainage networks in terms of meshness, and studied the relationship between topology and node flooding, finding that networks with higher meshness had fewer and shorter flood events at nodes, and smaller overflow volumes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lu et al [21], in a comparative study of branched and looped drainage pipes in Dongying, China, found that the peak runoff at the outlets of looped systems was significantly lower than that of branched networks. Subsequently, Lu et al [22] developed a framework for the optimal network structure of UDSs considering pipe redundancy, and the results showed that the total overflow volume of UDSs with looped pipes was reduced by 20% to 30%. Reyes-Silva et al [23] described the topological structure of drainage networks in terms of meshness, and studied the relationship between topology and node flooding, finding that networks with higher meshness had fewer and shorter flood events at nodes, and smaller overflow volumes.…”
Section: Introductionmentioning
confidence: 99%
“…The LI is achieved by adding pipes to streets where no pipes currently exist, thereby fully connecting the pipeline layout originally built around the block into a looped structure [22,24]. It is noteworthy that, because the base graph encompasses all possible drainage pipe connections, these structures, when reflected in the UDS, represent the opposite operation to the loop-opening mentioned in Section 2.2.…”
Section: Redundancy Intervention 231 Loop-introducingmentioning
confidence: 99%